Ignition and Self-Supporting Burning of Gas-Air Mixtures with Hydrogen Admixtures on Platinum Wire - Kalinchak, V. V.; Chernenko, A. S.; Sofronkov, A. N.; Fedorenko, A. V. (Physics and Chemistry of Solid State, 2017)
The proposed work describes analytical identification of hydrogen admixture concentration and catalyst temperatures limit values beyond which catalytic flameless steady combustion of gas-air mixtures at ambient temperature at platinum wires is observed. The effect of gas-air slip velocity upon considered values is shown. Initial platinum wire preheating temperatures required for catalytic ignition are determined.